1976
DOI: 10.54991/jop.1976.992
|View full text |Cite
|
Sign up to set email alerts
|

Upper Triassic sporae dispersae from the Tiki formation: Megaspores from the Janar nala section, South Rewa Gondwana basin

Abstract: Twenty-one different types of megaspores belonging to 10 genera are recorded from the plant-bearing bed in the upper part of the Tiki Formation exposed in a stream section in Bijouri-Harai area, Shahdol District, Madhya Pradesh (South Rewa Gondwana Basin). Five species are new. The genus Banksisporites Dettmann has been emended and enlarged. On the basis of megaspore study an Upper Triassic age for the plant-bed of the Tiki Formation is supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The material for the present investigation comprises pinnules of two taxa, possibly belonging to the Corystospermaceae, recovered from bulk maceration of a Late Triassic grey argillaceous shale exposed on the east bank of the Janar Rivulet, about 1 kilometer south-south-west of Harai Village (23°40'53" N: 81°12'40" E, Text-figure 1) in the South Rewa Basin. This shale, placed in the Tiki Formation, is rich in palynofossils (Banerji et al, 1978;Kumaran & Maheshwari, 1980), on the basis of which it is dated as Norian (Maheshwari et aI., 1978). Pal (1984) reported gymnospermous compression fossils from this shale, and identified Lepidoptensmadagascarensis, Dicroidium hughesii, D. zuben, Xyloptens sp., Sphenobaiera janarensis and Baiera sp.…”
Section: Methodsmentioning
confidence: 99%
“…The material for the present investigation comprises pinnules of two taxa, possibly belonging to the Corystospermaceae, recovered from bulk maceration of a Late Triassic grey argillaceous shale exposed on the east bank of the Janar Rivulet, about 1 kilometer south-south-west of Harai Village (23°40'53" N: 81°12'40" E, Text-figure 1) in the South Rewa Basin. This shale, placed in the Tiki Formation, is rich in palynofossils (Banerji et al, 1978;Kumaran & Maheshwari, 1980), on the basis of which it is dated as Norian (Maheshwari et aI., 1978). Pal (1984) reported gymnospermous compression fossils from this shale, and identified Lepidoptensmadagascarensis, Dicroidium hughesii, D. zuben, Xyloptens sp., Sphenobaiera janarensis and Baiera sp.…”
Section: Methodsmentioning
confidence: 99%
“…Indian Mesozoic Gondwana megaspores are reported by Sukhdev (1961), Singh et al, (1964), Maheshwari & Banerji (1975), Banerji et al (1978), Pant & Basu (1979), Banerji et al (1984), Jana & Ghosh (1997, Pal et al (1997), Patil &Premchand (2001) andJana (2004). Forty five genera are reported from Indian Gondwana of which thirty two genera are reported from Permian and thirteen from Mesozoic.…”
Section: Introductionmentioning
confidence: 92%
“…Horstisporites biswasii Paxilitriletes battenii HughesisporitesHorstiporites aerolatusBanerji et al 1984Banerji et al 1984 singhii (Harris 1935)Banerji et al 1984 Potonie 1956Late TriassicJhariatriletes obscurus Horstisporites aerolatusBanerji et al 1978(Harris 1935) Potonie 1956Early TriassicMaiturisporites distinctus Trikonia emarginata Pantiella bharadwajii Talchirella dubia…”
mentioning
confidence: 99%
“…2, 3) are listed below. Banerji et al, 1978 Banksisporites indicus (Singh, 1953) Tewari & Maheshwari, 1992 (Pl. 2.1, 2.2) Banksisporites utkalensis (Pant & Srivastava, 1961 Banksisporites sp.…”
Section: Megasporesmentioning
confidence: 99%
“…Records of megaspores from the Sohagpur Coalfield are rare. Besides, the records from the Barakar Formation by Bharadwaj and Tiwari (1970), Banerji et al (1978) reported megaspores from the Tiki Formation of Shahdol District. In the present paper, mega and microspores are reported for the first time from the Barakar Formation of the Dhanpuri Open Cast Mine (DOCM), Sohagpur Coalfield, Shahdol District, Madhya Pradesh.…”
Section: Introductionmentioning
confidence: 98%